The Algerian Revolution in the Records of the Lebanese Parliament 1958-1962 (Journal of the College of Basic Education, 2022)
The Lebanese Parliament is a legislative and constitutional institution, and its decisions bear the obligatory character of the successive governments that assumed the reins of power in Lebanon. They presented their positions on these developments during the course of the discussions, and the deputies emphasized support for the Algerian revolution and the adoption of a firm position in support of the independence movement, as well as issuing statements of protest and denunciation of the actions carried out by the French authorities and their army against the rebellious Algerian people, and the Council also provided material support accompanied by support It is a sincere human expression of the authentic Arab spirit that the members of the Lebanese parliament showed in defending the rights of the Algerian people, and the parliamentarians expressed their happiness for the great achievement that was achieved on March 19, 1962, when the French government agreed to a cease-fire that was considered by many. It is the great shift towards independence, which was achieved on July 3, 1962.